Study of modern solutions for improving land preparation works on agricultural land in Uzbekistan - Avezbaev Sadulla; Soatov Oybek; Sharipov Sayfiddin (E3S Web of Conferences)
The article critically evaluates the impact of recent reforms on agricultural lands and proposes contemporary solutions to enhance their efficient utilization. By analyzing the outcomes of these reforms, it identifies the practical challenges faced in land organization and management. The study underscores key issues, such as land fragmentation, soil degradation, and inefficient water usage, which impede optimal productivity. Through a comprehensive examination of current practices and innovative approaches, the article puts forth strategies for addressing these problems. These strategies encompass adopting advanced agricultural technologies, improved land management techniques, and sustainable farming practices. The proposed solutions aim to bolster land productivity, promote environmental sustainability, and ensure the long-term viability of agriculture. The article emphasizes the need for a coordinated effort among policymakers, farmers, and stakeholders to implement these solutions effectively. By fostering collaboration and knowledge exchange, the agricultural sector can surmount existing challenges and achieve a more sustainable and productive future. This research offers valuable insights into the ongoing discourse on agricultural land reforms and provides practical recommendations for their successful implementation.